CONSUMER ATTITUDE TOWARDS ECO-FRIENDLY PRODUCTS WITH SPECIAL REFERENCE TO TRIVANDRUM CITY - Sajeena, H.; Azhakeswari, S.A. Deepa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the current scenario, understanding the attitude of customers towards eco-friendly products holds immense importance due to the rise of eco conscious consumerisms particularly among the younger generation, where ethical and environment consideration play a major role in their purchasing decision. As consumers increasingly realise the importance of eco product, the marketers are also seeking to promote sustainability. So the present study was conducted with the primary focus on analysis of consumer attitude towards eco-friendly products among the consumers. A sample of 250 respondents from Trivandrum city was selected by purposive sampling technique and analysed with the help of statistical tools such as percentage analysis, Chi-square test and Garrett’s ranking technique. The findings of the study help the marketers to adapt strategies to meet evolving consumer expectations, promotes sustainable consumption pattern based on consumer attitudes, contributes broader environmental objectives and fosters a more responsible and eco conscious future.